STUDY ON THE IMPLEMENTATION OF THE CODE OF ETHICS FOR FINANCIAL REPORTING BASED ON LOCAL WISDOM OF BUGIS CULTURE "MALEMPU' NA MAPACCING" IN TELLUMPANUA DISTRICT, PINRANG REGENCY - Herawati; Bahri, Andi; Syarifuddin, Ahmad Dzul Ilmi (Islamic Financial And Accounting Review, 2023)
The Subdistrict Fund is an additional DAU (General Allocation Fund) budgeted by the Government in the State Revenue and Expenditure Budget for Fiscal Year 2019. However, the large subdistrict fund process is actually not in line with its good management. In fact, there are still many cases of misappropriation of sub-district funds in several areas. Local wisdom can be used as a basis for overcoming this problem, one of which is the local wisdom of the Bugis tribe's life values, namely malempu' na mapaccing. The research method used is a descriptive qualitative method. The data sources used are primary data, the data of which was obtained directly from interviews with parties who are competent in managing the Tellumpanua Village Fund, Suppa District and secondary data obtained from books, documents and journals/previous research theses which are related to this research. The data analysis techniques consist of data reduction, data presentation, andverification/drawing conclusions. The research results show that first,The Tellumpanua Subdistrict Government uses an accounting system to manage subdistrict funds. There are two accounting systems used, namely manual and through input into a special application, namely SIKD (Regional Financial Information System). Then the report is made at the end of the year by explaining the LPJ and then forwarded to the sub-district, then to the district, then to the province and finally to the center. Second, the local wisdom of malempu' na mapaccing is the basis for managing sub-district funds where the sub-district government strives to have honesty and cleanliness in reporting sub-district finances.